Biochemical properties of type I sourdough affected by wheat bran dietary fibre during fermentation. (6th September 2021) - Wang, Zhen; Ma, Sen; Huang, Jihong; Li, Li; Sun, Binghua; Tian, Xiaoling; Wang, Xiaoxi
Summary: The supplementation of dietary fibre in sourdough is beneficial to increase the nutritional quality of fermented foods. The influence of different wheat bran dietary fibre (WBDF) levels (0%, 3%, 6%, 9%, and 12%) on the biochemical characteristics of sourdough during fermentation was investigated. This study showed that WBDF was slightly resistant to the reduced pH caused by the initial fermentation of sourdough dough. After 6 h of fermentation, whether or not it contained WBDF, the dough's amylase activity was relatively stable ( P  > 0.05). However, in the samples containing WBDF, it took longer for the amylase activity to increase from 200 to 300 U g −1 . The content of free amino acids in the dough showed a tendency to first decrease and then increase with the metabolic activity of microorganisms, and WBDF could accelerate this rate. This study also provided evidence that insoluble dietary fibre may stimulate the growth and reproduction of lactic acid bacteria. Abstract : WBDF affects the biochemical properties of the fermentation process by resisting the reduction of pH in the system and by promoting the growth of microorganisms.